Optimization of Pipe Production Scheduling in Line 18 Using First Come First Serve (Fcfs), Earlier Due Date (Edd), Short Process Time (Spt) Methods (Case Study: Pt Wtur) - Mohamad Rizal Fadli; Wiwik Sulistiyowati (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2019)
For machine line 18, is intended to produce PVC pipe with a 5 ", 6" and 8 "with each contained item type AW and type D with a turn of the cycle a certain schedule. From the turn of this cycle, there are a couple of the impact is too long good finish duration of vacant stock in the Warehouse Production (GHP) pipe. The impact of the long duration of the good stock of empty finish unachieved impact on consumer demand (in this case the agent). By not reaching the consumer demand impact on service level SCM & Delivery. The purpose of this study to determine the optimal level of machine line 18 so that the products PVC size 5 ", 6" and 8 "are produced to meet the buffer stock storage. Thus, this research is expected to make a production schedule to meet the stock warehouse to the fullest, can meet the needs of consumers (agent) to the maximum but not over. From the data and data analysis using the First Come First Serve (FCFS), Earlier Due Date (EDD), Short Process Time (SPT), the SPT method is the most optimal method by having an average completion time of 4,10 days with 36,75% utility, then the average number of jobs 2,77 work, and delays the average occupation is 0,42 days.